Abused Men: Intimate Partner Violence in Anglo-American Literature - John Johnathan N Normandia; Andrea Uella B Falcunit; Riza Mae J Capitle; Genaro H Ferrariz; Kathryn B Normandia (Research Synergy Foundation Press, 2025)
Abuse is fair to no one—not even men. While the literature often highlights abuse against women, this study focused on abused men and the feminist defense in William Faulkner’s “A Rose for Emily”, Geoffrey Chaucer’s “The Wife of Bath’s Prologue”, and Edgar Allan Poe’s selected poems. Specifically, this addresses the types of abuse the male characters receive from their female counterparts, the impacts of the abuse on the male victims in the story, and how women justified such abuse. Using content and discourse analysis, characters, themes, and textual evidence (narrative structure, character interactions, and language) in the mentioned literary works were analyzed from the perspectives of masculinity studies and critical feminist theory. Key findings indicated that male characters experienced physical, emotional, psychological, sexual, and economic torture, which caused them to develop psychological trauma and even led to their death. Although these supported the narrative that women were equally capable of abusing men, the feminist point of view framed their actions as self-defense and coping mechanisms for personal trauma. This research contributes to a more critical understanding of gender-based violence and challenges the limitations of legal frameworks that often overlook male victimhood. Further, this can help craft inclusive and effective programs and support services catering to marginalized male victims. This method is also useful for literary scholars interested in gender-based abuse in literature and increases students’ awareness of gender roles—encouraging them to develop impartial views on intimate partner violence (IPV) scenarios.